Factors influencing spectator attendance in sports: a comparison between Kedah FA and Johor Darul Takzim fans (JDT FC) / Ellail Ain Mohd Aznan ... [et al.] - Mohd Aznan, Ellail Ain; Awang, Nor Shamira Awang; Abu Bakar, Al Hafiz; Md Yusof, Mohd Khairulanwar; Mohd Rosli, Norfaezah; Mohd Yazid, Siti Amalina (Universiti Teknologi MARA, Perlis, 2022)
One of the biggest draws for people watching a game at any sporting facility or stadium is the scenery. The quality of the sport scape will influence the enjoyment of viewers attending the match; this study focuses on the sport scape factors influenced by KEDAH FA and JDT FC fans’ attendance. The purpose of this study is to identify the differences in sport scape characteristics that influenced attendance between Kedah FA and Johor Darul Takzim fans (JDT FC). A total of 380 questionnaires were handed out to Kedah FA and JDT FC supporters. The instrument’s questionnaire for this study was based on the sport scape variables and attendance motivation. The results demonstrate a significant difference in attendance motivated by sport scape variables between Kedah FA and Johor Darul Takzim (JDT FC) fans (p<0.05), with JDT FC fans having a higher mean of 3.10 compared to Kedah FA fans who had a mean of 2.68. According to the survey, JDT FC fans are more motivated to attend the match due to the high quality of the sporting environment. This study agrees that sport scape features will drive spectators to visit the stadium or sports facility; nevertheless, future research could focus on other variables such as satisfaction.